Book Reviews (Journal of Finance, 1996)
Book reviewed in this article: Investments: A Visual Approach: Volume 1: Modern Portfolio Theory (text) and CAPM Tutor (software). By JOHN O'BRIEN and SANJAY SRIVASTAVA. International Financial Markets and the Firm . By PIET SERCU and RAMAN UPPAL. Finance Theory and Asset Pricing . By FRANK MILNE. Market Microstructure Theory . By MAUREEN O'HARA. Corporate Governance . By ROBERT MONKS and NELLS MINOW. Pension Schemes and Pension Funds in the United Kingdom . By DAVID BLAKE.